Ischemia Modified Albumin and D-dimer in the Diagnosis of Testicular Torsion: An Experimental Model - Sarac, Fatma; Yeniocak, Selman; Erbin, Akif; Yucetas, Esma; Altundal, Kamile; Ucpinar, Burak; Saygili, Ayse; Koldas, Macit (Urology Journal, 2019)
Purpose: We aimed to investigate the potential early diagnostic value of ischemia modified albumin (IMA) and D-dimer in testicular torsion. Material and Methods: A total of 42 prepubertal Wistar-Hannover rats (26-30 days old, weighing 75-125 grams) were used in the study. They were randomly divided into 2 groups as torsion (21 rats) and control (21 rats). Both torsion and control groups were subdivided into three subgroups as 30th, 120th and 240th minutes. Intraperitoneal injection of 70 mg/kg ketamine (Ketalar, Pfizer, Istanbul, Turkey) plus 10 mg/kg of xylazine (Rompun, Bayer, Istanbul, Turkey) were used for general anesthesia. In the control group, scrotal incision was made and the left testis gently extracted. Then, intracardiac blood and testicular tissue were obtained at 30th, 120th and 240th minutes. In torsion group, testicular ischemia was achieved by rotating left testis 720° clockwise and maintained by fixing the testis. Blood and testicular samples were obtained at 30th, 120th and 240th minutes. All animals were sacrificed after completion of the study. Results: There was a statistically significant difference between the IMA and D-dimer levels at 30th, 120th and 240th minutes of torsion group when compared with the control group (p = .001). When compared in terms of pathological changes at 30th, 120th and 240th minutes, significant difference was found for all 3 periods (p = 0.039, p = 0.014, p = 0.03, respectively). The D-dimer and IMA estimated torsion with reasonable accuracy [Area under the curve (AUC)= 0.771 (p = 0.003, 95% confidental interval: 0.620-0.922) and AUC = 0.706 (95% confidental interval: 0.549-0.863, p = 0.022), respectively. Conclusion: The elevated D-dimer and IMA serum levels observed in the experimental testicular torsion model seem to have a potential role as a serum marker in the early diagnosis of testicular torsion.